Behavior of Internal Customer in Family Business: Strategies and Actions for Improving Their Satisfaction - Gutiérrez-Broncano, Santiago; Jiménez-Estévez, Pedro; del Carmen Zabala-Baños, María (Frontiers in Psychology, 2017)
Determining the relevant aspects of family businesses that make them increasingly competitive is the main objective of researchers in this field. Despite this, there is little empirical literature on the behaviour of the internal customer in family businesses or how businesses increase their satisfaction. Basing our work on psychological theories and with both quantitative and qualitative information from 31 semi-structured interviews, this work establishes certain characteristics of the internal customers of the family business and proposes a series of guidelines for increasing their satisfaction, thereby facilitating the continuity of this type of business. Family businesses that are able to understand that the motivation of their internal customers is more important than other qualities, and that this requires a more comprehensive management will be able to get sustainable competitive advantages in the future.